Causes, consequences, and management of tree spatial patterns in fire-frequent forests - Ziegler, Justin Paul, author; Hoffman, Chad, advisor; Ocheltree, Troy, committee member; Redmond, Miranda, committee member; Rocca, Monique, committee member (Colorado State University. Libraries, 2022)
Increasingly, restoration treatments are being implemented to dually meet wildland fire hazard reduction alongside ecological objectives. Restoration treatments however deviate from conventional fuels treatments by emphasizing the re-creation of forest structure present prior to EuroAmerican settlement, notably the retention of single and grouped trees interspersed between canopy openings. As these historical forests persisted over cycles of fire returns, it is assumed that restoring these historical complex tree spatial patterns will, in turn, restore historical ecological processes. This includes more benign fire behavior that results in only partial tree mortality, allowing persistent and partial retention of forest cover over cycles of fire return. The qualitative description of historical forest structure, lacks, however, a clear process-based explanation detailing the interactions of heterogeneous forest structures and fire. While fires were historically frequent, it is unclear what role fire played in the genesis and maintenance of tree spatial patterns. If models of tree spatial dynamics can be improved and the interactions between tree spatial patterns and fire can be elucidated, forest managers will have an improved understanding of the implications of restoration-based fuels hazard reduction treatments both during fire-free periods and during fire events. The aims of this dissertation were to: 1) explore the causes of tree spatial patterns in dry fire-frequent forests; 2) investigate the consequences of tree spatial patterns on potential fire behavior and effects; 3) determine how alternate silvicultural strategies targeted at manipulation of tree spatial patterns can influence fire behavior and effects. In Chapter 2, I explored spatial patterns of tree regeneration over 44 years in absence of fire. In cooler periods, regeneration preferred clustering in openings, including openings following overstory mortality and away from overstory trees. Mortality risk of regeneration was heightened nearer overstory trees. In warmer periods, these trends reversed, likely because of a 'nurse effect' from the overstory. In anticipation of climate change, these results suggest silviculturists may benefit by capturing regeneration mortality in within openings while keeping regeneration near the overstory. In Chapter 3, I found that regenerating trees also form heterogeneous patterns following stand-replacing fires. In these sparse, early seral forests, all species were spatially aggregated, partly attributable to the influence of topography and beneficial interspecific attractions between ponderosa pine and other species. Results from this study suggest that scale-dependent, and often facilitatory, rather than competitive, processes act on regenerating trees. In Chapter 4, I studied the interaction between fire and tree spatial patterns, both historically and in modern forests. Tree mortality in the historical period was clustered and density-dependent because tree mortality was greater among small trees, which tended to be assembled in tightly spaced clusters. Tree mortality in the contemporary period was widespread, except for dispersed large trees, because most trees were a part of large, interconnected tree groups. Postfire tree patterns in the historical period, unlike the contemporary period, were within the historical range of variability found for the western United States. This divergence suggests that decades of forest dynamics without significant disturbances have altered the historical means of pyric pattern maintenance. In Chapter 5, I examined how fuels treatment designs with different manipulations of tree spatial patterns may influence treatment effectiveness. I simulated fires on hypothetical cuttings which manipulated the arrangement of crown fuels horizontally and vertically, either increasing the distance between tree crowns or not, and either removing small trees or not. All cutting methods reduced fire behavior and severity, but the results confirm possible tradeoffs between ecological restoration and hazard reduction; treatments that separated tree crowns reduced severity the most because these treatments reduced crown fire spread. But these can easily be overcome where restoration treatments incorporate small tree removal, because this action limits crown fire initiation. Managers could also incorporate managed fires to reduce surface fuel loads and use more aggressive cuttings to further gains in hazard reduction, regardless of cutting method used.
Keywords: physics based fire model; ponderosa pine; wildland urban interface fire dynamics simulator; point pattern analysis; frequent fire; wildland fire